THE EFFECTS OF COMPANY SIZE, COMPANY RISK AND AUDITOR’S REPUTATION ON TENURE: AN ARTIFICIAL ROTATION TESTING - Junaidi .; Novia Nurul Khasanah; Nurdiono . (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
This study aims to empirically examine the effects of firms’ size, firms’ risk, and auditors’ reputations on tenure in an artificial rotation. The phenomenon of artificial auditor (audit firm) rotations in Indonesia is an interesting topic, deserving further study. Artificial auditor rotations indicate a condition in which, conceptually, there has been a change of auditor that makes the relationship between the auditor and the client end, but in effect, the relationship is still going on. Regulations for mandatory auditor rotations causes audit firms or their partners to cheat the system by changing the name of their firm, or partners, to allow them to continue auditing the same client. This research samples 110 companies listed on the Indonesian Stock Exchange between 2000 and 2010, which were obtained using a purposive sampling method. The results of a statistical test indicate that a company’s size significantly influences the tenure. The variables of firms’ risk and auditors’ reputations do not have significant effects on tenure, statistically. This research is expected to contribute both theoretically and practically, especially to the regulations on auditors’ rotations. Auditing quality is an important factor that must be maintained by the auditor profession, to maintain the independence of auditors. In the auditing practices in Indonesia, regulators should consider the artificial rotation phenomenon that occurs in Indonesia, so the practice of auditing can run better.